Pluralidade cultural: visibilidades e silenciamentos Discursivos nas relações étnico-raciais no cotidiano escolar da EJA - Araújo Júnior, Ivo Teixeira de (2016)
The theme of Plurality is related to the analysis and valuation of ethnic and cultural concepts of the most diverse social groups inserted in socioeconomic inequalities and excluding social relations. For this reason, it is imperative that there be recognition of this plurality, especially those related to race, sexuality and gender. It is with this understanding that the proposed research aims to problematize and discuss discursivities that elaborate meanings, in narratives of teachers and students, about the deal with the coexistence with the ethnic-racial diversity, in the context of a municipal public school of João Pessoa-PB . Thus, it is asked how the statements of teachers and students construct meanings that translate the treatment of diversity in this school context, specifically those related to the identity matrices of racial ethnicity. The research is of a qualitative nature and, methodologically, it was used some procedures, such as questionnaires, interviews and conversation, as well as articulating Foucaultian theorizations about power relations, French discourse analysis (AD) conceptions of French affiliation and Of Cultural Studies. It is part of Applied Linguistics and adopts the concept of language as a social practice (MOITA LOPES, 2006).